Teacher's Strategy in Overcoming Students' Moral Decadence through Character Education - Rohmah, Siti Arifatur; Diana, Eka (Jurnal Simki Pedagogia, 2023)
This research was conducted based on obtaining a description of the teacher's strategy in overcoming the moral decadence of students through character education and obstacles in its implementation with the locus of MTs Nurul Jadid Paiton Probolinggo. The research method uses descriptive qualitative to get a detailed and credible picture of the teacher's strategy in overcoming the phenomenon of student moral decadence. The main subjects of the research include the principal, the student affairs department, class teachers, and several students as part of the research sample. Data were collected using participant observation techniques, in-depth interviews, and documentation. The Miles-Huberman interactive model was used as the data analysis procedure, which includes data collection, data presentation, data reduction, and conclusion drawing. The research analysis results show that efforts to overcome moral decadence carried out through character education by teachers with habituation, learning integration, and school culture application. Efforts to implement character education are not limited to being carried out by principals and teachers, but also all school components ranging from educational parts, environment, family, and pesantren. This series of steps is an effort and strategy to overcome moral decadence in MTs Nurul Jadid Paiton Probolinggo.